IMPLEMENTASI E-COMMERCE DALAM INDUSTRI PARIWISATA - Juita L D Bessie (Journal of Management Small and Medium Enterprises (SMEs), 2019)
Indonesia Tourism has huge potential and is a promising sector to be developed, as long asthe potential development is supported by a comprehensive planning and development byinvolving the utilization of internet technologies. One evidence of the rapid development ofICT is the internet presence. The internet has prompted us to enter the era of all digitally ecommerce.Even today, we are in the era of the industrial revolution 4.0. The industrialrevolution 4.0 will give the effect to shorten the distance between manufacturer and its targetmarket. Digital-based business activity known as the e-commerce in the era of industry 4.0is penetrated various fields including the tourism industry. E-tourism is an interactive onlinesystem enabling tourists to get information and booking some of the provided tourismelements such as hotels and travel agents. Implementation of e-tourism can be done throughthe website, social media, online advertising, web forums, smartphone applications.Through the e-tourism, it makes easier for travelers to travelling with automatic and multilanguage system. The utilization of ICT in the era of the industrial revolution 4.0 and thetourism world not only changing the paradigm of the industry, but also changing the job,the way to communicate, shopping, transaction, and lifestyle. Keywords: ICT, Internet, e-Commerce, e-Tourism